Association between academic stress and emotional eating among final-year thesis students in Aceh: A cross-sectional study - Ichsan Ichsan; Alfridsyah Alfridsyah; Agus Hendra Al Rahmad; Iswha Brilianti (AcTion: Aceh Nutrition Journal, 2026)
Final-year university students are recognized as a population vulnerable to academic stress, particularly during the thesis-writing phase, with previous studies reporting high stress prevalence and associated maladaptive behaviors. However, evidence specifically examining emotional eating during this high-risk phase in Aceh remains limited. This study aimed to analyze the relationship between academic stress and emotional eating among final-year students. A quantitative cross-sectional study was conducted in November–December 2024, involving 50 final-year students selected through total sampling, representing the entire eligible population. The inclusion criteria were active students completing their thesis, while incomplete responses were excluded. Academic stress and emotional eating were measured using the Indonesian versions of the Educational Stress Scale for Adolescents (ESSA) and the Emotional Eater Questionnaire (EEQ), which demonstrated acceptable internal consistency. Data were analyzed using the Spearman’s correlation test. Most respondents experienced moderate academic stress (80%), while emotional eating was predominantly moderate (54%) and severe (46%). A significant positive correlation was found between academic stress and emotional eating (rₛ = 0.33; p = 0.018). In conclusion, academic stress was moderately associated with increased emotional eating behavior among final-year students, highlighting the need for targeted stress management and behavioral interventions in the university setting.